2016
DOI: 10.4236/ojepi.2016.61008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Depression among Married Women Living in Urban Squatter Settlements of Karachi, Pakistan

Abstract: Background: Depression is one of the growing public health concerns among women worldwide. This is one of the most under-recognized and under-treated mental illnesses worldwide. Women of developing countries are inexplicably affecting with depression. Purpose: The purpose of study is to assess the prevalence and associative factors of depression among women of aged 20 to 40 years living in urban squatter settlements of Karachi, Pakistan. The identification of all the potential determinants will potentially hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The studies regarding depression among women have shown that increasing age among women is significantly associated with depression [ 29 , 37 ]. A Pakistan study reported a 1.8% increase in the prevalence of depression with every one-year increase in age [ 38 ]. The present study supported this finding and was shown to be a significant factor in the multiple logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The studies regarding depression among women have shown that increasing age among women is significantly associated with depression [ 29 , 37 ]. A Pakistan study reported a 1.8% increase in the prevalence of depression with every one-year increase in age [ 38 ]. The present study supported this finding and was shown to be a significant factor in the multiple logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…They may also have limited social support, contributing to stress-related health problems. The loss of a spouse or the end of a marriage can trigger depression and anxiety, potentially leading to disability 38 . Unmarried women might also have a higher prevalence of chronic health conditions like heart disease, stroke, and diabetes, which can further increase the risk of disability 37,39 .…”
Section: Discussionmentioning
confidence: 99%
“…A sample size of 340 participants was estimated through WHO sample size calculator and the formula for specified absolute precision, was utilized. The anticipated prevalence for this calculation was kept at 33%, based on a previous study [ 11 ]. The data was analyzed using descriptive statistics and correlation analysis, to examine the prevalence and severity of depression symptoms among the participants.…”
Section: Methodsmentioning
confidence: 99%
“…In Pakistan, the prevalence of depression among women ranges from 29% to 66%, while for men, it varies from 10% to 33%. [ 11 ]. According to the existing published work, determinants of women health in Pakistan include marital status, social support, inter-spousal communication, educational levels and family type [ 12 ].…”
Section: Introductionmentioning
confidence: 99%